Peran Unit Pengumpulan Zakat (UPZ) Masjid Modern Kurir Langit dalam Menanggulangi Kemiskinan di Kabupaten Barru: The Role of the Zakat Collection Unit (UPZ) of the Modern Mosque of the Sky Courier in Overcoming Poverty in Barru Regency - Wahyudin, Wahyudin; Trisno Wardy Putra; Nurfiah Anwar (TIJARAH: Jurnal Ekonomi, Manajemen, dan Bisnis Syariah, 2025)
This research is a descriptive qualitative study conducted at the Amil, Zakat, Infaq, and Alms Institution of the Sky Courier Mosque in Barru Regency. The approach used is phenomenological, with the aim of exploring and explaining individual experiences related to economic empowerment carried out by mosques. The results of the study show that the role of mosques in economic empowerment does not significantly reduce poverty levels if assessed only in terms of economic results, but succeeds in carrying out their main functions. The BMT (Baitul Maal wat Tamwil) program is the most accessed by the public compared to other economic programs.